Zimbabwe school examinations council online mark capturing and grading system - Mhute, Nancy Vongai (Midlands State University, 2019)
The first chapter gives a summary of the ZIMSEC as an organisation, when it was formed and its relevant operations. The objectives that led to the research are also crafted in this chapter together with the justification for the study. Different types of feasibility were carried out to ascertain whether it was viable to continue with the system development and an analysis was done for all types of risks that might be encountered. The analysis phase focused on fact finding and different methodologies such as observations and interviews were used to gather information about how the current system was operating and what the users expected. Data flow diagrams for the current system showing how data flowed between different entities were also crafted and functional and non-functional requirements were discussed. After gathering facts about the old system and its weaknesses, the design for the new system was laid out that is physically and logically. Different output and input forms for the system were drafted to make the user have a clear picture on how the new system and its interfaces will be displayed. The implementation as the final phase illustrated different testing strategies conducted before the system was deployed to users. Training sessions timetable was drafted and various types of maintenance discussed together with the recommendations for maintenance and to stakeholders of the system training was carried out at ZIMSEC and the internal employees were given hands on experience with the system. Maintenance schedules were put in place after user training. Recommendations were also documented for further or future developments and this then will give an opportunity and ideas to the organisation in the future to improve the system